2010
DOI: 10.1186/1471-2229-10-184
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the Vitis viniferaPR10 multigene family

Abstract: BackgroundGenes belonging to the pathogenesis related 10 (PR10) group have been studied in several plant species, where they form multigene families. Until now, such an analysis has not been performed in Vitis vinifera, although three different PR10 genes were found to be expressed under pathogen attack or abiotic stress, and during somatic embryogenesis induction. We used the complete genome sequence for characterising the whole V. vinifera PR10 gene family. The expression of candidate genes was studied in va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 40 publications
5
64
0
Order By: Relevance
“…Three conserved residues related to ribonucleolytic activity of PR-10 proteins also existed in RhPR10.1 protein, including Glu (E) at amino acid position 96, 148, and Tyr (Y) or His (H) at 150 (Supplemental Fig. S3A; Lebel et al, 2010). The two conserved features above suggest that RhPR10.1 may have RNase activity.…”
Section: Rhpr101 Inhibits Ethylene-induced Rose Flower Senescence Thmentioning
confidence: 87%
See 1 more Smart Citation
“…Three conserved residues related to ribonucleolytic activity of PR-10 proteins also existed in RhPR10.1 protein, including Glu (E) at amino acid position 96, 148, and Tyr (Y) or His (H) at 150 (Supplemental Fig. S3A; Lebel et al, 2010). The two conserved features above suggest that RhPR10.1 may have RNase activity.…”
Section: Rhpr101 Inhibits Ethylene-induced Rose Flower Senescence Thmentioning
confidence: 87%
“…We isolated a 766-bp RU06312 cDNA sequence with a 477-bp predicted open reading frame by rapid amplification of cDNA ends, encoding a deduced protein of 159 amino acids with a conserved P-loop motif and Bet v 1 motif (Lebel et al, 2010;Supplemental Fig. S3).…”
Section: Resultsmentioning
confidence: 99%
“…surveyed. The conservative logic taken came to an estimation of three to four copies of PR-10 genes in each Oxytropis genome whereas there are 10 PR-10 genes from G. max (Schmutz et al 2010), 8 from (Handschuh et al 2007), 13 from Betula pendula (Schenk et al 2006), 14 (nine functional) from Vitis vinifera (Lebel et al 2010), 18 from Malus domestica (Gao et al 2005), 8 from Prunus persica and P. dulcis (Chen et al 2008) and 8 from Fragaria ananassa (MusidlowskaPersson et al 2007). The three to four diVerent paralogs of ripening-related proteins we discovered in Oxytropis are also a slightly lower count than in other Fabaceae Schmutz et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…in apple [24], peach [30] and poplar [31] PR-10 genes. Lebel et al [22] found that thirteen out of the seventeen Vitis vinifera PR-10 sequences are present on the chromosome in direct orientation suggesting that most copies were produced by unequal crossing over events, as described in Arabidopsis and rice [32]. Gene duplication events in the genome evolution process make new copies of a gene which may undergo modifications resulting in functional diversification [33].…”
Section: Pr-10 Proteins: An Overviewmentioning
confidence: 99%
“…PR-10 genes are multi gene families having low intra specific variation but higher inter specific variation which makes them interesting phylogenetic markers [22]. For example, at least five PR-10 genes in pea [23], eighteen Mal d 1 genes in apple [24], ten Bet v 1 genes in birch [25] They also tend to form physical clusters on specific chromosomes, e.g.…”
Section: Pr-10 Proteins: An Overviewmentioning
confidence: 99%